The Role of Pragmatics in Cross-Cultural Communication - Smith, George (European Journal of Linguistics, 2024)
Purpose: The general purpose of this study was to explore the role of pragmatics in cross-cultural communication. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings reveal that there exists a contextual and methodological gap relating to pragmatics in cross-cultural communication. The study provided valuable insights into the pivotal role of pragmatics in facilitating effective communication across diverse cultural contexts. By exploring principles such as speech acts, politeness strategies, and implicature, the research enhanced understanding of how language is used and interpreted in cross-cultural interactions. The findings underscored the importance of pragmatic competence and cultural sensitivity in achieving mutual understanding. Furthermore, the study highlighted the need for incorporating pragmatic awareness training into educational curricula and policymaking efforts to promote cultural inclusivity and cooperation. Overall, the study's contributions deepen our understanding of cross-cultural communication dynamics and offer practical guidance for navigating cultural differences in an interconnected world. Unique Contribution to Theory, Practice and Policy: Speech Act theory, Politeness theory and Relevance theory may be used to anchor future studies on the role of pragmatics in cross-cultural communication. The study provided several key recommendations that contributed to both theory and practice in the field of intercultural communication. These recommendations included incorporating pragmatic competence training into educational curricula, implementing cross-cultural training programs in organizations, developing initiatives and policies to promote intercultural understanding, considering cultural factors in online communication platforms, engaging in reflective practices to enhance awareness of cultural differences, and establishing cross-cultural pragmatics as a distinct field of study. These suggestions aimed to enhance individuals' ability to navigate cross-cultural interactions effectively, promote inclusivity and mutual understanding in diverse settings, and advance theoretical knowledge in the field of intercultural communication.